The Effect Of Work Discipline And Work Motivation On The Performance Of Courier PT. Ninja Express Tasikmalaya - Teguh Ginanjar; Kusuma Agdhi Rahwana; Arga Sutrisna (Journal of Indonesian Management, 2022)
The purpose of this study is determine the effect simultaneously and partially between Work Discipline and Work Motivation on Courier Performance PT. Ninja Express Tasikmalaya. The research method used is a survey method with a quantitative approach. The sampling technique used the saturated sample method with a total sample of 40 peoples. Data collection techniques using online questionnaires. The data used is primary data. The analytical tool used in this study is multiple regression using SPSS 26. The results show that work discipline and work motivation have a significant effect on performance simultaneously. Partially, work discipline has a significant effect on performance. Partially, work motivation has a significant effect on performance.